Jahresbericht 1996 - Magazin [1] = Annual Report. - Amanshauser, Hildegund; Bauer, Ute Meta; Giese, Herbert; Graninger, Wolfgang; Graw, Isabelle; Klein, Erich; Krön, Peter; Ressler, Oliver; Schnyder, Jean-Frederic; Scholten, Rudolf; Schulmeister, Stephan; Snauwaert, Dirk; et al. (Salzburg : Salzburger Kunstverein, 1997)
Dertschei, Eva ; Feldbacher, Sigrid ; Hruza, Dominik ; Hundsbichler, Gottfried ; Jeanée, Pascale ; Kandl, Johanna ; Leikauf, Andreas ; Mitterhuber, Manuela ; Müller, Ulrike ; Ressler, Oliver ; Thater, Diana ; Schnyder, Jean-Frederic ; Tuerlinckx, Joëlle ; Zinggl, Wolfgang
biografie, bibliografie
Duits & Engels
boek